Spirituality, Mental Health and Quality of Life: Pathways in Indian Psychology - Pant, Naveen (Springer Nature Singapore, 2023)
1. Introduction;- 2. Spirituality, Mental Health and Quality of Life: An Introduction -- 3. The Relationship of Spirituality with Mental Health and Quality of Life: A Review -- 4. The Role of Spirituality in Predicting Mental Health and Quality of Life Among Early Adults -- 5. Indian Psychology of Mind and Mental Health.